Analysis and Suggestions on Current Situation of Fire-fighting Facilities for Urban Rail Transit. (2018) - Yang, Jun-tao; Liang, Jing; He, Qi-ze
Abstract: Fire-fighting facilities are important components to ensure the fire safety in public facilities. However, with the increasing service time of major urban subways, serious fire safety issues are raised in more and more urban rail transit facilities. In this study, the current situation of urban rail transit fire-fighting facilities is investigated through field research and information searching. The common problems concerning the urban rail transit fire-fighting facilities is summarized, including the aging of equipment, improper maintenance, divorcement of design, construction and operation, and improper operation of equipment. Some suggestions for improvements are offered in the end.